Elotuzumab and dexamethasone for relapsed or refractory multiple myeloma patients: A retrospective study. (25th April 2018) - Gross, Zachary; Rahbari, Ashkon; Wirtschafter, Eric; Spektor, Tanya M.; Udd, Kyle A.; Bujarski, Sean; Ghermezi, Michael; Nosrati, Jason D.; Vidisheva, Aleksandra; Eades, Benjamin; Cecchi, Gary; Maluso, Tina; et al.
Abstract: Objective: To evaluate the efficacy and safety of elotuzumab and dexamethasone (Ed) for relapsed or refractory multiple myeloma (RRMM) patients. Method: This retrospective study evaluated the efficacy and safety of Ed treatment for 21 RRMM patients, 11 of whom were considered lenalidomide‐refractory, and all of whom had progressed on at least 1 prior steroid‐containing regimen. We also evaluated the efficacy of adding lenalidomide to a subset of patients following progression from Ed. Results: The overall response rate (ORR) and clinical benefit rate (CBR) of Ed were 10% and 19%, respectively. An additional 52% of patients demonstrated stable disease as their best response. The median PFS was 1.8 months on Ed for all patients. Fifteen patients received ERd following progression on Ed, and 60% of these patients were lenalidomide‐refractory. The ORR and CBR were 20% and 33%, respectively, and the median PFS was 3.4 months. Conclusion: Our results suggest that some patients can benefit from Ed without an accompanying immunomodulatory agent and that efficacy can be achieved with the addition of lenalidomide at the time of progression. No new safety signals were detected, except for thrombocytopenia in 1 patient on Ed.